2020
DOI: 10.1182/blood.2019002639
|View full text |Cite
|
Sign up to set email alerts
|

Feed-forward regulatory loop driven by IRF4 and NF-κB in adult T-cell leukemia/lymphoma

Abstract: Adult T-cell leukemia/lymphoma (ATL) is a highly aggressive hematological malignancy derived from mature CD4+ T-lymphocytes. Here, we demonstrate the transcriptional regulatory network driven by 2 oncogenic transcription factors, IRF4 and NF-κB, in ATL cells. Gene expression profiling of primary ATL samples demonstrated that the IRF4 gene was more highly expressed in ATL cells than in normal T cells. Chromatin immunoprecipitation sequencing analysis revealed that IRF4-bound regions were more frequently found i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
52
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(54 citation statements)
references
References 64 publications
2
52
0
Order By: Relevance
“…Indeed, NF‐ĸB signalling is an important pathway in T‐ALL cells, whereby sirtuin1 can physically interact with and deacetylate the NF‐ĸB subunit of p65/RELA at lysine 310 residue, thus resulting in transcriptional inhibition 7 . Moreover, NF‐κB which is recognized as an important factor in normal inflammatory, immune and carcinogenesis, is found to be activated in T‐ALL 8 . Importantly, activation of NF‐κB in cancer‐associated leucocytes drives cytokine secretion that facilitates metastasis via activation of the C‐X‐C chemokine receptor type 7 (CXCR7) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, NF‐ĸB signalling is an important pathway in T‐ALL cells, whereby sirtuin1 can physically interact with and deacetylate the NF‐ĸB subunit of p65/RELA at lysine 310 residue, thus resulting in transcriptional inhibition 7 . Moreover, NF‐κB which is recognized as an important factor in normal inflammatory, immune and carcinogenesis, is found to be activated in T‐ALL 8 . Importantly, activation of NF‐κB in cancer‐associated leucocytes drives cytokine secretion that facilitates metastasis via activation of the C‐X‐C chemokine receptor type 7 (CXCR7) 9 .…”
Section: Introductionmentioning
confidence: 99%
“…In ATLL cells, somatic mutations are frequently found in genes in the TCR signaling pathway [ 7 ]. These mutations precede development of detectable disease, can accumulate in predominant clones over many years, are not found in HTLV-1 infected patients who fail to develop ATLL [ 11 ] and signal though NFκB to interferon regulatory factor 4 (IRF4) [ 12 ]. The IRF4 gene is the most frequently mutated gene in ATLL, with 1 in 4 patients carrying amplification of the IRF4 gene and 1 in 7 individuals acquiring activating nucleotide variants [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Highly expressed in ATLL, IRF4 drives cellular proliferation [ 13 , 14 ] and is associated with poor prognosis and therapeutic resistance [ 15 , 16 ]. IRF4 and NFκB have been described as master regulators of transcription in ATLL, forming a coherent feed-forward loop that drives cell proliferation and survival [ 12 ]. The downstream targets of IRF4 and its mechanism of action in ATLL pathogenesis remains largely uncharacterized.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, besides its potential immunosuppressive properties (31), IL-10 promotes proliferation of HTLV-1-infected cells through the STAT3 and IRF4 pathways (25). Interestingly, it was demonstrated that IRF4 and NF-κB drive ATL maintenance (32). Similarly, a recent study showed that the HTLV-1 anti-sense bZIP factor HBZ upregulates expression of IL-10, interacts with STAT1 and STAT3 and modulates the IL-10/JAK/STAT signaling pathway (33).…”
Section: Discussionmentioning
confidence: 99%